Sinergitas Nahdlatul Ulama dan Muhammadiyah Dalam Pengembangan Ekonomi Islam di Indonesia - Faishol Luthfi; Wildana Latif M. (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
This paper aims to analyze the sinergity of Islamic organisations (Nahdlatul Ulama and Muhammadiyah) towards the development of Islamic Economy in Indonesia. This study uses a qualitative method. This type of research is literature analysis. Data is collected and analyzed from the main sources of Islam (i.e. Qur'an and Hadith) and previous research studies related to Islamic organizations in Indonesia. The authors find that Nahdlatul Ulama and Muhammadiyah are the largest Islamic organizations in Indonesia which have their own characteristics. Both of these organizations have a distinction in the methods of da'wah and mass bases. The synergy of Nahdlatul Ulama and Muhammadiyah through da'wah methods and mass bases can develop Islamic economy in Indonesia. The authors argue that in the future it may be necessary to have a deeper synergy between activists, administrators, and followers of Nahdlatul Ulama and Muhammadiyah. This paper is the pioneer to analyze the sinergity of Islamic organizations towards the development of Islamic Economy in Indonesia.